THE IMPURITY OF SHARIAH BANKING IN INDONESIA - Januari Pratama Nurratri Trisnaningtyas (Journal of Sharia Economics, 2022)
The practice of Islamic banking should run accordingly with the rule of sharia. Islamic banking aimed to overcome conventional banking problems, which are often profit-driven and benefit only a particular party. In Indonesia, where the majority of the population is Muslims, Islamic banking runs together with conventional banking and creates a dual-banking system. This dual-banking system seems fair on the one hand. However, it causes challenges in terms of the pure practice of Islamic banking, on the other hand. This research analyses the implementation of Islamic banking in Indonesia within the dual-banking system through three main frameworks: the regulation of Islamic banking, Islamic banking’s product to compete with the conventional ones, and the government regulation regarding this matter. The research shows that Indonesia has not been able to implement Islamic banking in accordance with the sharia rules fully. Instead, some principles are adapted according to the dual-banking system and are aligned with the interest of various parties such as the government and central bank of Indonesia.